Diary of an ltalian artist in India : synchrony of opposites - Bocchi, Simona (New Delhi : Har-anand publications, 2021)
During her long stay in India she explores new external landscapes that remodel her own interior landscape through her practice of conscious attention, and she offers herself to the reader as a companion for an extraordinary introspective journey.
Includes index.
Keywords: Literature; Sculptors - India - Biography